Volar Approach to the First Extensor Compartment for Surgical Treatment of DeQuervain Tenosynovitis. Issue 2 (June 2021) - Park, Adam Y.; Smith, Dean W.
Abstract : Many surgical techniques have been published in regards to the operative management of DeQuervain tenosynovitis. As it has been classically described, stenosing tenosynovitis of the first extensor tendon compartment is a common tendinopathy along the radial side of the wrist causing pain and swelling in the affected area. When surgery is necessary, decompression of the abductor pollicis longus and extensor pollicis brevis tendons decreases first extensor compartment friction and has been shown to successfully alleviate symptoms. A number of varying techniques have been reported in the literature to achieve adequate decompression and minimize postoperative complications such as sensory nerve injury, incomplete decompression, and tendon subluxation. We describe a novel volar approach to the first extensor compartment, which allows direct visualization of the retinaculum and a midline retinacular release. In addition, the volar approach has an associated decreased risk of iatrogenic nerve injury by passing volar and deep to the more superficial sensory nerves that overly the retinaculum. On the basis of our experience, patients do not experience an increased risk of volar tendon subluxation with this approach.